Optimization of culture conditions to enhance mycophenolic acid biosyntheis by Penicillium brevicompactum BB263 isolated in Vietnam - Pham, Thanh Huyen; Bach, Thi Mai Hoa; Dang, Thi Thuy Duong; Le, Thi Minh Thanh; Pham, Thanh Ha; Chu, Thanh Binh; Nguyen, Phuong Nhue (Vietnam Journal of Biotechnology, 2025)
Mycophenolic acid (MPA) is an immunosuppressant utilized in organ transplantation to prevent rejection and in the treatment of autoimmune diseases such as Crohn's disease and systemic lupus erythematosus. Previous studies have reported that MPA is predominantly produced by fungal strains of the genus Penicillium, exhibiting immunosuppressive, antiviral, and antitumor activities, making it valuable in medical applications. In this study, we present the optimization of nutritional components in the fermentation medium for the fungal strain Penicillium brevicompactum BB263 to enhance MPA biosynthesis. Experiments were designed using the Box-Behnken methodology to assess the effects of three factors–sucrose, yeast extract, and methionine–on MPA production. The optimized medium for P. brevicompactum BB263, designated as YES-F1, comprises (per liter): sucrose 38.14 g, yeast extract 18.69 g, methionine 1.29 g, glycine 4 g, and trace elements 1 mL. Fermentation conditions include an initial pH of 6.5, a temperature of 25°C, an agitation speed of 200 rpm, and a harvest time of 114 hours post-inoculation. Following optimization, MPA production increased tenfold compared to the initial YES medium, reaching 969.79 µg/mL, corresponding to a yield exceeding 70% relative to the biomass of P. brevicompactum BB263. These findings provide a foundation for the industrial-scale production of MPA from Penicillium strains in Vietnam.